Identifikasi Keanekaragaman Famili Kenikir-Kenikiran (Asteraceae) di Kawasan Desa Kawak Pakis Aji Jepara - Azzarkasyi, Anang Khoirunni'am; Widyaningrum, Fitri; Afsari, Hanisa Ayu; Ni'mah, Nazilatun; Jalil, Muhamad (Universitas Negeri Semarang, 2024)
Indonesia is one of the countries that has the highest level of biodiversity in the world. However, there are still many plants in Indonesia whose species have not been identified. This causes the need to identify and classify plants. This research aims to identify the diversity and dominance of plant species from the Asteraceae family in Kawak Village, Batealit District, Jepara Regency. This study was carried out on May 28, 2023 and June 1, 2023. The method used was the exploration method by determining sampling locations at 21 points from 3 hamlets in Kawak village. The tools and materials needed for this research include an accurate altimeter version 2.3.2, ziplock plastick, newsprint, cellphone camera, meter and internet access. There are 6 plant species from the Asteraceae family, including Wedelia trilobata, Crassocephalum crepidioides, Elephantopus scaber, Chromolaena odorata, Synedrella nodiflora, and Ageratum conyzoides. The plants obtained were collected using the herbarium method. The dominant plant species from the Asteraceae family in Kawak village is tapak Liman (Elephantopus scaber).